EUTHANASIA IN INDONESIAN CRIMINAL LAW AND HEALTH LAW - HENNY SAIDA FLORA (Jurnal MHKI, 2022)
The problem of euthanasia is part of the actions of a doctor who is treating his patient or asking for his help so that a person's illness can be cured. In terms of legislation, there is no new and complete regulation on euthanasia, but because the issue of euthanasia involves the issue of the safety of the human soul, a legal basis must be sought. The purpose of this research is to find out Euthanasia which is regulated in the Indonesian Criminal Law and Health Law. Therefore, the only legal basis used is Article 344 of the Criminal Code because it is considered close. The method used is a normative juridical method with a statutory approach. The results show that in principle not everyone agrees with the act of euthanasia as well as doctors. Some community groups start on a religious basis, so that everything is the will of God. The arguments put forward by the doctors are in accordance with the Indonesian medical code of ethics which also reflects the attitudes or views of doctors in Indonesia regarding euthanasia.